Central ossifying fibroma in old female: A case report and review of literature - Hanaa Hezam Algadi; Widad Murajia Alqasi; Omer Mohammed Jamali (Wolters Kluwer Medknow Publications, 2018)
Central ossifying fibroma is a benign, non-odontogenic tumor of the jaw, a type of fibro-osseous lesion characterized by slow growth and proliferation of fibrous cellular tissue, bone, cement, or a combination. This lesion tends to occur in the second to fourth decades of life, with predilection for women and for the mandibular premolar and molar areas. The following article reports a case of a 49-year-old female patient, who presented with large ossifying fibroma in the mandible and brief literature review of these uncommon lesions is also conducted.